Batterer Programs: What Criminal Justice Agencies Need to Know (1998) - U.S. Department of Justice, Office of Justice Programs, National Institute of Justice (My University, 2016)
This NIJ Report provides judges and probation officers with basic information about batterer treatment program goals and methods. It summarizes the range of programming available (from mainstream to innovative approaches) throughout the country. (palabras claves: violencia intrafamiliar)